The Biopolitics of Biometrics: An interview with Btihaj Ajana. (December 2014) - Beer, David
As a result of a growing interest in neoliberal political economy, surveillance and new forms of data, questions around metrics and the governance of life are moving to the forefront of contemporary conceptual analysis. This particular interview draws upon the key themes from Btihaj Ajana's recently published book Governing through Biometrics: The Biopolitics of Identity (2013). Although the interview focuses centrally upon the book, it also covers broader topics including identity, measurement, the work of Foucault, big data, biopolitics, bioethics and biometrics. Ajana's book sketches out a valuable conceptual set of resources for thinking through these pressing issues, the interview looks to explore how such a set of resources might continue to develop.